1988
DOI: 10.1002/j.1460-2075.1988.tb02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the human B cell CD20 receptor predicts a hydrophobic protein with multiple transmembrane domains.

Abstract: CD20 is an antigen expressed on normal and malignant human B cells that is thought to function as a receptor during B cell activation. Here we report the isolation of a CD20‐specific cDNA clone from a lambda gt11 library using a polyclonal antiserum raised against purified CD20 antigen. Additional cDNA clones were then isolated from a lambda gt10 library. Alignment of the sequences of overlapping lambda clones reveal a single consensus sequence except for a divergence that preceded the first methionine within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(124 citation statements)
references
References 40 publications
0
122
0
2
Order By: Relevance
“…CD20 is found in healthy mature B cells as early as in the pro-B phase, as well as in chronic lymphocytic leukemia, LPHL and in some cases of classical HL. 4,10 It has a specific role in the regulation of differentiation and growth of B cells through cell activation from a resting state (G0) on to G1, as well as regulation of the cell cycle from the S phase to mitosis, step-by-step. 9 It is part of a cell-surface complex that regulates calcium transport and is able to initiate an intracellular signaling pathway through calcium influx.…”
Section: Cd20 Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD20 is found in healthy mature B cells as early as in the pro-B phase, as well as in chronic lymphocytic leukemia, LPHL and in some cases of classical HL. 4,10 It has a specific role in the regulation of differentiation and growth of B cells through cell activation from a resting state (G0) on to G1, as well as regulation of the cell cycle from the S phase to mitosis, step-by-step. 9 It is part of a cell-surface complex that regulates calcium transport and is able to initiate an intracellular signaling pathway through calcium influx.…”
Section: Cd20 Expression and Functionmentioning
confidence: 99%
“…9 It is part of a cell-surface complex that regulates calcium transport and is able to initiate an intracellular signaling pathway through calcium influx. [10][11][12] Nevertheless, disruption of calcium channel gene encoding does not demonstrate critical effects either on B-cell development or immune response implementation. 12 The presence of CD20 expression in lymphocytepredominant HL and some presentations of classical HL support the hypothesis that HRS cells derive from germinal-center B cells at the centroblast stage.…”
Section: Cd20 Expression and Functionmentioning
confidence: 99%
“…From the characterization of its encoding gene, CD20 has been predicted to be a 33-37-kd membraneassociated phosphoprotein, with a structure of 4 transmembrane regions, a 44-amino acid extracellular loop, and cytoplasmic N-and C-termini (3). Based on structural homologies, CD20 has been postulated to function as a calcium channel subunit (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although the function of CD20 has not yet been fully unraveled and CD20-knockout mice do not show a prominent phenotype, 9 CD20 does appear to play a role in Ca 2+ transport as cells transfected with CD20 increase their resting levels of intracellular Ca 2+ . [10][11][12] Some of the most interesting data on CD20 signalling comes from work showing that when crosslinked with MAb, CD20 is rapidly reorganized in the lipid bilayer membrane. 13 CD20 might be one of many signalling molecules (including the kinases Lyn, Fyn and Lck) able to divide into the sphingolipid and cholesterol-rich microdomains so important in antigen receptor signalling in lymphocytes.…”
Section: The Cd20 Targetmentioning
confidence: 99%
“…Grade III/IV toxicities included fever, infection, hemorrhage, nausea, vomiting, diarrhea, and stomatitis consistent with those seen in patients receiving BEAM alone. Engraftment for granulocytes was seen at a median of 10 days (range, [8][9][10][11][12][13][14][15][16][17] and for platelets on day 20 (range, . It was concluded that the addition of a therapeutic dose of 90 Y-ibritumomab to high-dose BEAM chemotherapy is likely to be without serious toxicity, and further phase II evaluation is ongoing.…”
Section: Rit With 90 Y-ibritumomab Tiuxetan (Zevalin) As Part Of the mentioning
confidence: 99%